Risk Tolerance Level among Working Adults in Kuala Lumpur, Malaysia - Bakri, Abdul Karim; Wenceslas, Cassandra Nisha; Muhammad Hafiz, Mohd Shukri (UNIMAS Publisher, 2016)
This paper examines the relationship between demographic factors such as gender, age, marital status, education level and income with the level of risk tolerance. We use a survey questionnaire from 147 respondents of working adults in Kuala Lumpur. The results show that the respondents prefer to keep/ invest in liquid assets such as savings account, cash in hand and Employment Pension Funds (EPF). This indicates that a majority of them are risk averse with a small percentage of respondents who invest in risky assets like gold, mutual funds/unit trust, real estate. Male respondents owned more risky assets, signifying that they are more risk tolerant than the female respondents. The study also shows that individuals with higher education levels, specifically tertiary education have greater risk tolerance. Results from the regression analysis show that only age and marital status are to be statistically significant to risk tolerance of working adults. This indicates that older respondents tend to be more risk adverse compared to the younger ones while the married respondents seem to be risk takers than the single ones.